Statistical data mining using sas applications - Fernandez, George , 1952- (Chapman & Hall/CRC data mining and knowledge discovery series, 2010)
Compatible with SAS version 9, SAS Enterprise Guide, and SAS Learning Edition, this resource describes statistical data mining concepts and methods and includes 13 user-friendly SAS macro applications for performing complete data mining tasks. Each chapter emphasizes step-by-step instructions for using SAS macros and interpreting the results